Top Lights - Bright Cities and their Contribution to Economic Development - Richard Bluhm; Melanie Krause (Center for Economic Studies and ifo Institute (CESifo), 2018)
The commonly-used satellite images of nighttime lights fail to capture the true brightness of most cities. We show that night lights are a reliable proxy for economic activity at the city level, provided they are first corrected for top-coding. We present a stylized model of urban luminosity and empirical evidence which both suggest that these `top lights' follow a Pareto distribution. We then propose a simple correction procedure which recovers the full distribution of city lights. Applying this approach to cities in Sub-Saharan Africa, we find that primate cities are outgrowing secondary cities but are changing from within.
Keywords: O10; O18; R11; R12; 330; development; urban growth; night lights; top-coding; inequality